Development and testing of an m-Health platform to reduce post-operative penetrative sex in recipients of voluntary medical male circumcision - Toefy, Mogamat Yoesrie (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.